Method for preparing high alpha phase alumina raw powder by aluminum ash wet denitrogenation and self-propagation

CN122916626APending Publication Date: 2026-10-16ZHEJIANG MEICHEN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611223720.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]本发明提供了一种铝灰湿法脱氮协同自蔓延制备高α相氧化铝原粉的方法,解决现有铝灰堆存污染环境、资源浪费,以及铝灰制备耐火材料时AlN脱除不彻底、盐分残留高、能耗高、产物纯度低的问题

Benefits of technology

(1)本发明实现铝灰资源化高效利用,环保无污染。以工业固废铝灰为唯一原料,实现铝灰中AlN、单质Al、Al2O3等有效组分的充分利用,彻底解决铝灰堆存带来的土地占用和环境污染问题;AlN反应生成的氨气用于辅助燃烧,盐分挥发后回收利用,无有毒有害气体、废水、废渣排放,环保效益显著;固废资源化利用率≥98%,实现变废为宝。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the field of industrial solid waste resource utilization and refractory material preparation, and particularly relates to a method for preparing high alpha phase alumina raw powder by wet denitrification and self-propagating combustion of aluminum ash. The method comprises the following steps: pretreating aluminum ash to obtain pretreated aluminum ash; spraying water vapor into the pretreated aluminum ash to perform wet denitrification reaction and recover ammonia gas, and obtaining denitrified aluminum ash; granulating the denitrified aluminum ash; mixing the denitrified aluminum ash particles and a self-propagating initiator to perform self-propagating initiation and ammonia gas assisted combustion high-temperature calcination, and obtaining high alpha phase alumina raw powder by crushing and grinding the calcination product. The present application solves the technical pain point that AlN and salt residues in the aluminum ash lead to poor performance of the refractory material, realizes efficient utilization of aluminum ash resources, has the advantages of simple process, low energy consumption, high product purity, environmental protection and energy saving, the technical principle is feasible, and is suitable for industrial large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of industrial solid waste resource utilization and refractory material preparation, and particularly to a method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash in a synergistic self-propagating manner. Background Technology

[0002] Aluminum ash is a major industrial solid waste generated by industries such as electrolytic aluminum, aluminum processing, and aluminum alloy smelting. It contains abundant effective components such as Al2O3 and elemental Al, but also salts such as AlN, sodium chloride, and potassium chloride, as well as impurities such as Fe2O3 and SiO2. AlN is toxic and produces ammonia gas upon contact with water, while the salts are hygroscopic. Direct stockpiling or landfilling not only occupies significant land resources but also causes air, water, and soil pollution, resulting in a serious waste of aluminum resources. Currently, the main methods for utilizing aluminum ash include recycling metallic aluminum, preparing building materials, and producing chemical products. However, these methods have several drawbacks: recycling metallic aluminum is complex and energy-intensive, and it cannot effectively remove AlN and salts; preparing building materials has low added value, and the harmful components in aluminum ash may affect the performance and safety of building materials; the production of chemical products requires high purity of aluminum ash, resulting in high pretreatment costs and hindering large-scale application.

[0003] Refractory materials are indispensable basic materials in industries such as metallurgy, chemical engineering, and building materials. Among them, high-alumina refractories are widely used in high-temperature kilns, metallurgical equipment, and other fields due to their advantages such as high temperature resistance, corrosion resistance, high strength, and good thermal conductivity. The main raw material for high-alumina refractories is α-alumina. The traditional method of preparing α-alumina mainly uses high-purity Al2O3 as raw material and prepares it through high-temperature calcination. This method has drawbacks such as high raw material cost, high energy consumption, and long production cycle, which limits its large-scale application.

[0004] The existing technology for preparing alumina powder from aluminum ash generally suffers from the following problems: First, the AlN in the aluminum ash is not completely removed, and the residual AlN reacts with water to produce ammonia gas, which can cause the refractory material to crack and pulverize, affecting the product performance; second, the salt in the aluminum ash cannot be effectively removed, and the salt absorbs moisture, which will reduce the strength and high-temperature resistance of the refractory material; third, the calcination process is energy-intensive, making it difficult to achieve the directional formation of α-alumina, resulting in low product purity, which cannot meet the requirements of high-alumina refractory materials; fourth, the ammonia gas produced by the reaction of elemental Al and AlN in the aluminum ash is not fully utilized, resulting in resource waste and environmental pollution.

[0005] Based on this, a method for preparing alumina powder from aluminum ash that is simple in process, low in energy consumption, thoroughly removes AlN and salts, and produces high-purity products is developed. This method achieves an organic combination of efficient utilization of aluminum ash resources and low-cost preparation of refractory materials, and has significant economic, social, and environmental benefits. Summary of the Invention

[0006] This invention provides a method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash and synergistic self-propagation, which solves the problems of environmental pollution and resource waste caused by existing aluminum ash storage, as well as the problems of incomplete AlN removal, high salt residue, high energy consumption and low product purity when aluminum ash is used to prepare refractory materials.

[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution: This invention provides a method for preparing high α-phase alumina powder by wet denitrification of aluminum ash and synergistic self-propagation, comprising the following steps: S1. Pre-treat the aluminum ash to obtain pre-treated aluminum ash; S2. Spray water vapor into the pretreated aluminum ash to carry out a wet denitrification reaction and recover ammonia gas, and obtain denitrified aluminum ash. S3. Granulate and dry the wet denitrified aluminum ash to obtain denitrified aluminum ash particles; S4. The denitrified aluminum ash particles are mixed with a self-propagating initiator and subjected to self-propagating initiation and ammonia-assisted combustion at high temperature to obtain high α-phase alumina particles.

[0008] S5. The high α phase alumina particles are crushed and ground to obtain high α phase alumina raw powder.

[0009] In some specific embodiments, in S1, the pretreatment includes: crushing aluminum ash to a particle size ≤10mm, and then sequentially performing grinding, magnetic separation for impurity removal, sieving, and drying.

[0010] In some specific embodiments, the grinding method is ball milling, and the ball milling process includes: a ball-to-material ratio of 8:1 to 11:1, a grinding speed of 350 to 480 r / min, and a grinding time of 2 to 3.5 hours; The conditions for magnetic separation to remove impurities are as follows: magnetic separation intensity is 0.3~0.45T, magnetic separation temperature is 10~30℃, magnetic separation is performed 2~3 times, and the time for each magnetic separation is 10~18min. The sieve mesh size for sieving is 120-150 mesh.

[0011] In some specific embodiments, in S2, the amount of water vapor injected is 5% to 12% of the pretreated aluminum ash, the water vapor is saturated steam or superheated steam, the atomized particle size of the water vapor is 5 to 20 μm, and the conditions for the wet denitrification reaction are: temperature of 120 to 150°C, time of 1.5 to 3 h, and pressure of 0.02 to 0.1 MPa.

[0012] In some specific embodiments, in S3, the amount of water added during granulation is 5-12% of the mass of the denitrified aluminum ash. The granulation process also includes adding a binder, which includes sodium carboxymethyl cellulose and / or starch. The granulation conditions are: ambient temperature of 25-35℃, ambient humidity of 40%-60%, rotation speed of 5-20 r / min, and time of 20-40 min.

[0013] In some specific embodiments, in S3, the drying conditions are: temperature of 80~95℃ and time of 0.5~1h.

[0014] In some specific embodiments, in S4, the mass ratio of the denitrified aluminum ash particles to the self-propagating initiator is 100:(2~6); the self-propagating initiator includes potassium nitrate and nitrogen-rich aluminum ash; in the nitrogen-rich aluminum ash, the mass content of elemental aluminum is 10%~20%, and the mass content of aluminum nitride is 20%~35%; the mass ratio of potassium nitrate to the nitrogen-rich aluminum ash is (3~5):1.

[0015] In some specific embodiments, the conditions for the self-propagation initiation are: heating from 10-30°C to 300°C at a heating rate of 5-8°C / min, then heating to 400-450°C at a heating rate of 3-5°C / min, and then heating to 550-590°C at a heating rate of 2-3°C / min; the conditions for calcination are: temperature of 1100-1300°C and time of 2-4 hours.

[0016] In some specific embodiments, in S4, the ammonia-assisted combustion process includes: mixing preheated ammonia and preheated air, and then introducing the mixture into a high-temperature calcining furnace for ammonia-assisted combustion.

[0017] In some specific embodiments, the temperature of the preheated ammonia is 200~300℃; the temperature of the preheated air is 300~400℃; the volume ratio of the preheated ammonia to the preheated air is 1:(8~12); the conditions for ammonia-assisted combustion are: temperature 1300~1500℃ and time 1~2h.

[0018] In some specific embodiments, after the ammonia-assisted combustion is completed in step S5, the process further includes: crushing the product obtained from the ammonia-assisted combustion to a particle size ≤100μm, and then sequentially screening, purifying, removing impurities and unqualified particles.

[0019] In some specific embodiments, the sieve mesh size for screening is 180-200 mesh; The purification method is two-stage magnetic separation for impurity removal. The conditions for the two-stage magnetic separation are: magnetic separation intensity of 0.3~0.4T, magnetic separation number of times of 1~2 times, and magnetic separation time of 8~12min for each time. The method for removing impurities and unqualified particles is to feed the magnetically separated powder into an air classifier, with a classification speed of 2000-3000 r / min and a classification airflow velocity of 15-25 m / s.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention achieves efficient utilization of aluminum ash resources in an environmentally friendly and pollution-free manner. Using industrial solid waste aluminum ash as the sole raw material, it fully utilizes the effective components such as AlN, elemental Al, and Al2O3 in aluminum ash, completely solving the land occupation and environmental pollution problems caused by aluminum ash stockpiling; the ammonia gas generated by the AlN reaction is used for auxiliary combustion, and the salt is recovered and reused after volatilization, with no toxic or harmful gases, wastewater, or waste residue emissions, resulting in significant environmental benefits; the solid waste resource utilization rate is ≥98%, realizing the transformation of waste into treasure.

[0021] (2) This invention has low energy consumption and significantly reduces production costs. It utilizes the self-propagating combustion of elemental Al in aluminum ash to release heat, eliminating the need for a large amount of additional energy consumption and reducing calcination energy consumption; the raw material is inexpensive industrial solid waste, reducing raw material costs by more than 70% and significantly enhancing the market competitiveness of the product.

[0022] (3) The process of this invention is simple and easy to operate, making it suitable for large-scale industrial application. The entire process flow is clear and the reaction parameters are controllable. The technologies such as raw material pretreatment, pelletizing, wet denitrification, self-propagating combustion, ammonia-assisted combustion, and post-treatment are all mature and feasible industrial technologies. The equipment requirements are moderate and do not require complex high-end equipment. The production cycle is short (16-24 hours in total), easy to operate, and easy to achieve large-scale industrial production. At the same time, the process parameters can be adjusted according to the differences in aluminum ash composition to adapt to different types of aluminum ash.

[0023] (4) The present invention has a high resource recycling rate and significant economic benefits. The ammonia generated by the AlN reaction is used to assist combustion and realize energy recovery; the salt is recovered and used in the chemical industry after volatilization; the iron impurities removed by magnetic separation can be recycled and reused; there is no resource waste in the entire production process, realizing full-process resource recovery and further improving economic benefits; the prepared high α phase alumina raw powder has high added value, large market demand, and good industrialization prospects.

[0024] (5) The present invention has high reaction stability and no safety hazards. Through real-time temperature monitoring and compensation technology, excessive temperature fluctuations during self-propagating combustion and ammonia-assisted combustion are avoided; safety protection measures are adopted in the ammonia collection, storage and combustion processes to avoid ammonia leakage; no flammable, explosive or toxic substances are generated in the entire production process, and the operation is safe and reliable. Detailed Implementation

[0025] The present invention will be described below through specific embodiments. Those skilled in the art will understand that the specific embodiments described below are for illustrative purposes only and do not limit the scope of the invention in any way. Furthermore, in the following embodiments, unless otherwise specified, the reagents and equipment used are commercially available. If specific processing conditions and methods are not explicitly described in the following embodiments, conditions and methods known in the art can be used for processing.

[0026] This invention provides a method for preparing high α-phase alumina powder by wet denitrification of aluminum ash and synergistic self-propagation, comprising the following steps: S1. Pre-treat the aluminum ash to obtain pre-treated aluminum ash; S2. Spray water vapor into the pretreated aluminum ash to carry out a wet denitrification reaction and recover ammonia gas, and obtain denitrified aluminum ash particles. S3. Granulate and dry the aluminum ash particles to obtain denitrified aluminum ash particles; S4. Mix the denitrified aluminum ash particles with a self-propagating initiator, and perform self-propagating initiation and ammonia-assisted combustion high-temperature calcination to obtain high α-phase alumina particles. S5. The high α phase alumina particles are crushed and ground to obtain high α phase alumina raw powder.

[0027] This invention discloses a method for preparing high-α-phase alumina raw powder using wet denitrification of aluminum ash in conjunction with self-propagating initiation technology. The method involves pretreatment of aluminum ash, wet denitrification process, self-propagating initiation technology, and ammonia-assisted combustion technology. This achieves efficient removal of AlN, complete separation of salts, and directional formation of α-alumina from the aluminum ash. Simultaneously, ammonia and salts are recycled, reducing energy consumption. The resulting high-α-phase alumina raw powder meets the requirements for high-purity, high-Al2O3 raw materials for refractory materials. In detail: Pretreatment of aluminum ash removes impurities (Fe2O3, SiO2, soluble impurities, etc.), optimizes particle size distribution, increases specific surface area, and enhances reactivity, laying the foundation for subsequent wet denitrification, pelletizing, and high-temperature calcination. The pretreated aluminum ash undergoes a wet denitrification reaction, allowing AlN in the ash particles to fully react with mist-like water vapor, generating aluminum hydroxide and ammonia, achieving efficient AlN removal. The denitrified aluminum ash is then granulated into uniform spherical particles, increasing the contact area with the initiator and preventing particle agglomeration or collapse during subsequent reactions, ensuring uniform self-propagating combustion. Then, the elemental Al in the aluminum ash is ignited by a self-propagating initiator. The heat released by the spontaneous combustion of elemental Al increases the temperature inside the kiln, achieving energy saving and consumption reduction. At the same time, it promotes the initial crystallization of Al2O3, laying the foundation for the subsequent formation of α-alumina. Finally, ammonia and air are mixed and burned to increase the temperature at the kiln tail, achieving complete volatilization and separation of salts in the aluminum ash. At the same time, it promotes the directional conversion of Al2O3 into α-alumina, improving the purity of the product.

[0028] In some embodiments, in S1, the aluminum ash contains 5% to 15% AlN by mass, 3% to 10% elemental Al by mass, and 50% to 70% Al2O3 by mass. The impurities in the aluminum ash include metal salts, Fe2O3, and SiO2. The metal salts mainly include sodium chloride and potassium chloride, with a total mass content of 3% to 8%.

[0029] In some embodiments, S1, the pretreatment includes: crushing aluminum ash to a particle size ≤10mm, and then sequentially performing grinding, magnetic separation for impurity removal, sieving, and drying.

[0030] In this invention, pretreatment with aluminum ash can remove impurities (Fe2O3, SiO2, soluble impurities, etc.), optimize the particle size distribution of aluminum ash, increase the specific surface area, and enhance the reactivity of aluminum ash, laying the foundation for subsequent pelletizing, wet denitrification and high-temperature calcination.

[0031] In this invention, the crushing method is not specifically limited; any conventional crushing method in the art can be used to ensure that the particle size of the crushed aluminum ash is ≤10mm. In some embodiments, a jaw crusher can be used for crushing. Crushing removes large inert impurities (such as unreacted aluminum blocks, rock fragments, etc.) from the aluminum ash, facilitating subsequent grinding. After crushing, a vibrating screen (10 mesh) is used for preliminary screening to remove excessively large inert impurities, reducing the subsequent grinding load.

[0032] In some embodiments, the particle size of the ground aluminum ash is ≤75μm.

[0033] In this invention, the grinding method is not specifically limited; any conventional grinding method in the art can be used to ensure that the particle size of the ground aluminum ash is ≤75μm. In some embodiments, the grinding method is ball milling, in which the ground aluminum ash is fed into a planetary ball mill with a ball-to-material ratio of 8:1 to 11:1, a grinding speed of 350 to 480 r / min, a grinding time of 2 to 3.5 h, and grinding until the aluminum ash particle size is ≤75μm. During the grinding process, the mill can be stopped and stirred every 30 minutes to ensure uniform grinding and avoid excessively large local particles.

[0034] In some embodiments, the iron impurity content in the aluminum ash after magnetic separation is ≤0.8wt%.

[0035] In this invention, the conditions for magnetic separation are not specifically limited; conventional magnetic separation conditions in the art can be used to ensure that the iron impurity content in the aluminum ash after magnetic separation is ≤0.8wt%. In some embodiments, the conditions for magnetic separation are: magnetic separation intensity of 0.3~0.45T, magnetic separation temperature of 10~30℃, magnetic separation times of 2~3 times, and magnetic separation time of 10~18min per time. Magnetic separation separates and removes iron impurities such as Fe2O3 from the aluminum ash, resulting in an iron impurity content of ≤0.8wt% in the aluminum ash after magnetic separation. The iron impurities after magnetic separation can be recycled and reused, improving resource utilization. After magnetic separation, a blower can be used to blow away the aluminum ash powder to remove fine iron filings adsorbed on the surface.

[0036] In some embodiments, the sieve mesh size is 120-150 mesh.

[0037] In some embodiments, the proportion of particles with a diameter of 120-150 mesh in the sieved aluminum ash is ≥95%.

[0038] In this invention, the specific screening process includes: finely screening the magnetically separated aluminum ash powder through a 120-150 mesh sieve, using ultrasonic-assisted screening (ultrasonic power 200-300W) to avoid sieve clogging, removing excessively large unground uniform particles and residual inert impurities, ensuring uniform aluminum ash particle size, and achieving an aluminum ash qualification rate ≥95% after screening; residual particles on the sieve are returned to the ball mill for regrinding to improve raw material utilization.

[0039] In some embodiments, the moisture content of the dried aluminum ash is ≤0.5wt%.

[0040] In this invention, the drying method is waste heat from flue gas or hot air drying. The drying conditions are: temperature 110~130℃, time 1.5~2.5h. The moisture content of the dried aluminum ash is ≤0.5%. Excessive drying temperature will cause the elemental Al in the aluminum ash to oxidize, affecting subsequent self-propagating combustion. The dried aluminum ash is cooled to room temperature to obtain pretreated aluminum ash for later use.

[0041] In this invention, during the pretreatment process, the aluminum ash is crushed and ground to increase its specific surface area, thereby improving the reaction efficiency of subsequent wet denitrification, self-propagating combustion, and high-temperature calcination. Magnetic separation can remove iron impurities such as Fe2O3 from the aluminum ash, preventing them from affecting the high-temperature resistance and purity of the refractory material. Sieving can ensure that the aluminum ash has a uniform particle size, avoiding uneven reaction caused by particle size differences.

[0042] In some embodiments, in S2, the wet denitrification reaction can be carried out in high-temperature furnaces such as vertical furnaces and horizontal rotary kilns, and has the ability to operate intermittently and continuously. Preferably, the wet denitrification reaction device is a pre-denitrification reactor, which is equipped with a temperature monitoring device (accuracy ±5℃), an atomizing device, and an ammonia collection device. The atomizing device uses high-pressure atomizing nozzles, with 3-6 nozzles evenly distributed on the inner wall of the pre-denitrification reactor to ensure uniform spraying of atomized water vapor. The ammonia collection device includes a condenser, a bag or ceramic dust collector, and a pressure-resistant storage tank for collecting and purifying ammonia. Before the reaction, the pre-denitrification reactor is preheated to 80℃ under no-load to remove moisture and impurity gases from the furnace, and the atomizing device and ammonia collection device are checked for normal operation.

[0043] In some embodiments, the specific process of S2 includes: The aluminum ash particles are fed into a wet denitrification reactor with a filling thickness of 10-15 cm. If the filling thickness is too high, it will affect the contact between water vapor and aluminum ash, resulting in incomplete AlN reaction; if the filling thickness is too low, heat will be lost too quickly, increasing energy consumption. After filling, the pre-denitrification reactor is sealed to ensure good airtightness and prevent ammonia leakage. Water vapor is sprayed into the pre-denitrification reactor through an atomizing device to carry out the wet denitrification reaction.

[0044] In this invention, during the injection process, the furnace temperature and water vapor volume are monitored in real time to ensure that AlN reacts fully with water vapor and the AlN conversion rate is ≥99%.

[0045] In some embodiments, in S2, the amount of water vapor injected is 5% to 12% of the pretreated aluminum ash, the water vapor is saturated steam or superheated steam, and the atomized particle size of the water vapor is 5 to 20 μm.

[0046] In some embodiments, the conditions for the wet denitrification reaction are: temperature of 120~150℃, time of 1.5~3h, and pressure of 0.02~0.1MPa.

[0047] In some embodiments, the heating method in the wet denitrification reaction is a staged heating method, which involves heating from room temperature to 120°C at a heating rate of 4-6°C / min, and then heating to 130-150°C at a heating rate of 2-3°C / min, and then maintaining the temperature at a constant temperature for 1.5-3 hours.

[0048] In this invention, in the wet denitrification reaction, the ammonia gas generated by the reaction of AlN with water vapor enters the ammonia gas collection device through the exhaust port at the top of the pre-denitrification reactor; it is first cooled to near room temperature by a condenser tube, and then the trace dust and impurities in the ammonia gas are removed by bag filter or ceramic filter method, and the purity of the purified ammonia gas is ≥98%; the purified ammonia gas is stored in a pressure-resistant storage tank for later use.

[0049] In this invention, after the wet denitrification reaction is completed, the atomizing device is turned off, and the rotation speed of the pre-denitrification reactor is maintained to allow the denitrified aluminum ash particles to cool naturally to 80~100°C in the furnace, avoiding rapid cooling that could cause the particles to crack. After cooling, denitrified aluminum ash particles are obtained, with an AlN content of ≤1%, which are then set aside for later use.

[0050] In this invention, during the wet denitrification reaction, AlN undergoes a directed chemical reaction with mist-like water vapor at a high temperature of 120~150℃ to generate aluminum hydroxide and ammonia. The core reaction equation is as follows: AlN + 3H₂O → Al(OH)₃ + NH₃↑; The reaction can proceed spontaneously under normal pressure. The higher the temperature and the more fully the water vapor contacts the aluminum ash particles, the more complete the reaction. The atomized water vapor has a small particle size and uniform distribution, which can fully contact the aluminum ash particles and improve the AlN conversion rate. By controlling the amount of water vapor injected and the reaction temperature, the AlN conversion rate can be ensured to be ≥99%, and the ammonia production can be stable, providing sufficient fuel for subsequent auxiliary combustion.

[0051] In some embodiments, in S3, the mass ratio of the pretreated aluminum ash to the water is 100:(8~15).

[0052] In some embodiments, in S2, the mixing conditions are: a stirring speed of 10~30 r / min and a stirring time of 15~25 min, to ensure that the aluminum ash and water are fully mixed to form a uniform paste.

[0053] In some embodiments, the granulation process further includes adding a binder, wherein the amount of binder added is 0% to 0.3% of the mass of the denitrified aluminum ash, and the binder includes sodium carboxymethyl cellulose and / or starch. In this invention, when the viscosity of the pretreated aluminum ash mixed with water is insufficient, a binder can be added and stirring can be continued for 10 to 15 minutes to improve the viscosity and formability of the material.

[0054] In some embodiments, the granulation conditions in S3 are: ambient temperature of 25~35℃, ambient humidity of 40%~60%, rotation speed of 5~20r / min, and time of 20~40min.

[0055] In some embodiments, in S3, the particle size of the aluminum ash particles is 3~8mm.

[0056] In this invention, during the granulation process, a small amount of deionized water can be sprayed every 2 to 5 minutes to ensure that the granules are formed completely and have a smooth surface, and to avoid cracking or sticking of the granules. After granulation, a vibrating screen is used to screen the granules to remove granules that do not meet the size requirements. The unqualified granules are returned to the granulator for regranulation.

[0057] In some embodiments, in S3, the moisture content of the aluminum ash particles is ≤3wt%. In this invention, the drying conditions in S3 are not specifically limited. In some embodiments, in S2, the drying temperature is 80~95℃, and the drying time is 0.5~1h. Preliminary drying removes free moisture from the particle surface, preventing particle adhesion and improving particle strength. The dried particles are then cooled to room temperature for later use.

[0058] In this invention, pretreated aluminum ash is mixed with a small amount of water and an optional binder is added. The mixture is then granulated into spherical particles using a granulation device. This increases the contact area between the aluminum ash particles and the initiator, preventing the particles from collapsing during self-propagating combustion and ensuring a uniform reaction. Preliminary drying removes free moisture from the particle surface, preventing particle adhesion and improving particle strength.

[0059] In some embodiments, in S4, the mass ratio of the denitrified aluminum ash particles to the self-propagating initiator is 100:(2~6); the self-propagating initiator includes potassium nitrate and nitrogen-rich aluminum ash; in the nitrogen-rich aluminum ash, the mass content of alumina is 40%~60%, the mass content of elemental aluminum is 10%~20%, and the mass content of aluminum nitride is 20%~35%; the mass ratio of potassium nitrate to the nitrogen-rich aluminum ash is (3~5):1.

[0060] In some embodiments, during S4, the mixing conditions are: a rotation speed of 5-30 r / min and a mixing time of 15-20 min. This mixing process ensures that the initiator and aluminum ash particles are thoroughly mixed.

[0061] In some embodiments, S4, the conditions for the self-propagation initiation are: heating from 10~30°C to 300°C at a heating rate of 5~8°C / min, then heating to 400~450°C at a heating rate of 3~5°C / min, and then heating to 550~590°C at a heating rate of 2~3°C / min.

[0062] In some embodiments, in S4, the calcination conditions are: a temperature of 1100~1300℃ and a time of 2~4h.

[0063] In this invention, in step S4, a segmented heating method is used for self-propagating initiation. When the temperature rises to 550~590℃, the self-propagating initiator begins to burn, releasing a large amount of heat and igniting elemental Al in the aluminum ash. The elemental Al spontaneously combusts and releases a large amount of heat, causing the temperature in the middle of the kiln to rise rapidly to 1100~1300℃, and then it is calcined at a constant temperature for 2~4 hours. During the constant temperature calcination process, the temperature inside the kiln is monitored in real time. When the temperature fluctuation exceeds ±20℃, the heating power is adjusted to ensure temperature stability. During this process, aluminum hydroxide decomposes into Al2O3, and Al2O3 initially crystallizes.

[0064] In some embodiments, the specific process of S4 includes: The denitrified aluminum ash particles are cooled to 80~100℃ and fed into a double spiral agitator. A self-propagating initiator is added, and the aluminum ash particles mixed with the initiator are transferred to a rotary kiln (or roller kiln). The material filling thickness is 8-12cm, and self-propagating initiation and combustion are carried out.

[0065] In this invention, during the self-propagating initiation and calcination, the self-propagating initiator (potassium nitrate, nitrogen-rich aluminum ash) burns rapidly at 550-590°C, releasing a large amount of heat to reach the ignition point of elemental Al (approximately 550°C), igniting the elemental Al in the aluminum ash. The spontaneous combustion of elemental Al releases a large amount of heat, causing the temperature in the middle of the kiln to rise rapidly to 1100-1300°C without the need for additional energy consumption, thus achieving energy saving and consumption reduction. At this temperature, Al2O3 in the aluminum ash begins to crystallize, and aluminum hydroxide begins to decompose into Al2O3, laying the foundation for the subsequent formation of α-alumina. By controlling the reaction temperature, excessive oxidation of elemental Al during combustion is avoided, and side reactions of impurities are prevented, ensuring reaction stability.

[0066] In some embodiments, in S5, the ammonia-assisted combustion process includes: Preheated ammonia and preheated air are mixed and then introduced into a high-temperature calcining furnace for ammonia-assisted combustion.

[0067] In some embodiments, the temperature of the preheated ammonia gas is 200~300℃; the temperature of the preheated air is 300~400℃.

[0068] In this invention, the ammonia gas can be selected from the ammonia gas generated by the wet denitrification reaction in S3, and the ammonia gas generated by the AlN reaction can be used as auxiliary fuel to further reduce energy consumption. Compared with the traditional method of preparing high Al2O3 raw material for refractory materials, the energy consumption is reduced by more than 50%; the raw material is inexpensive industrial solid waste, reducing the raw material cost by more than 70%, which greatly enhances the market competitiveness of the product.

[0069] Ammonia gas is fed into a preheater and preheated to 200-300°C, which removes trace amounts of water vapor from the ammonia gas and improves combustion efficiency. At the same time, air is fed into an air preheater and preheated to 300-400°C to reduce heat loss during ammonia combustion.

[0070] In some embodiments, in S4, the volume ratio of the preheated ammonia to the preheated air is 1:(8~12). In this invention, the volume ratio of the preheated ammonia to the preheated air is 1:(8~12) to obtain a combustible mixture.

[0071] In some embodiments, in S4, the mixed gas obtained by mixing preheated ammonia and preheated air is supplied to the kiln tail where the product obtained after combustion is located in S4 through an injection device. The injection device is evenly distributed on the inner wall of the kiln tail to ensure uniform combustion of the mixed gas.

[0072] In some embodiments, in S4, the conditions for ammonia-assisted combustion are: a temperature of 1300~1500℃ and a time of 1~2h. In this invention, the combustion of ammonia mixed with air releases a large amount of heat, raising the kiln tail temperature to 1300~1500℃, and maintaining this temperature for 1~2h. The kiln tail temperature is controlled at 1300~1500℃; excessively high temperatures can lead to excessive growth of α-alumina grains, affecting refractory performance, while excessively low temperatures result in incomplete salt volatilization. During the constant-temperature calcination process, the kiln tail temperature is monitored in real time, and the flow rate of the mixed gas is adjusted to ensure temperature stability.

[0073] In some embodiments, in S4, at a high temperature of 1300~1500℃, the sodium chloride, potassium chloride and other salts in the aluminum ash completely volatilize and are discharged from the kiln with the exhaust gas; the exhaust gas enters the condensation recovery device, is cooled to below 100℃, the salts condense into solids, and a mixed salt of sodium chloride and potassium chloride is collected, which can be recycled for use in the chemical industry, realizing the resource utilization of salts; the condensed exhaust gas is purified (removing trace dust and harmful gases) before being discharged, meeting environmental protection standards.

[0074] In some embodiments, S4 further includes: after combustion, the product is discharged from the kiln tail and naturally cooled or air-cooled to room temperature; after cooling, the calcined product is obtained, the main component of which is α-alumina and the salt residue is ≤0.3%.

[0075] In this invention, during ammonia-assisted combustion, the ammonia gas generated by the AlN reaction in the wet denitrification process is combustible. After preheating, it is mixed with preheated air in a certain proportion and burned at the kiln tail, releasing a large amount of heat and raising the kiln tail temperature to 1300~1500℃. Under high temperature conditions, the sodium chloride, potassium chloride and other salts (boiling point 800~1000℃) in the aluminum ash will completely volatilize and separate, and be collected by a condensation recovery device to achieve salt recovery and utilization. At the same time, the high temperature of 1300~1500℃ can promote the directional conversion of Al2O3 into α-alumina (the stable generation temperature of α-alumina is above 1200℃), improving the purity and refractory properties of the product. The products of ammonia combustion are nitrogen and water, with no toxic or harmful gas emissions, making it environmentally friendly and pollution-free.

[0076] In some embodiments, S5, after cooling, the combustion products are obtained, and post-processing is also included, including: crushing the products obtained by ammonia-assisted combustion to a particle size ≤100μm, and then sequentially screening, purifying, removing impurities and unqualified particles to obtain high α-phase alumina raw powder, and then packaging and storing it. Among them, the particle size of the combustion products after crushing is ≤100μm. The crushing method can be to feed the calcined products cooled to room temperature into an impact crusher (or an air jet crusher). During the crushing process, the crushing speed is controlled at 2000~3000r / min to avoid over-crushing and powder agglomeration. After crushing, the powder is sent to a screening device by a vibrating conveyor. The screening method is ultrasonic-assisted screening, specifically: the crushed powder is screened through a 180~200 mesh screen while the ultrasonic generator (power 300~400W, frequency 20~40kHz) is turned on to avoid screen clogging and ensure screening efficiency; after screening, unqualified particles with excessively large particle sizes are removed and returned to the crusher for re-crushing; the qualified rate of the powder after screening is ≥98%; Purification involves secondary magnetic separation for impurity removal. Specifically, the sieved powder is fed into a high-intensity magnetic separator for secondary magnetic separation. The magnetic separation intensity is controlled at 0.3~0.4T, with 1~2 separations performed, each lasting 8~12 minutes. This removes iron impurities that were not completely separated during the calcination process, resulting in an iron impurity content of ≤0.5wt% in the powder after magnetic separation. The method for removing impurities and unqualified particles is to feed the magnetically separated powder into an air classifier, controlling the classification speed at 2000~3000 r / min and the classification airflow velocity at 15~25 m / s to remove fine impurities and agglomerated particles from the powder, ensuring uniform particle size. After classification, high α-phase alumina raw powder is obtained, with an α-alumina content ≥90%, salt residue ≤0.3%, and iron impurity content ≤0.5%, which meets the standard for high Al2O3 raw powder for refractory materials. The specific packaging and storage process is as follows: the high α phase alumina raw powder is sent into a drying oven and dried at 100~110℃ for 0.5~1h to remove trace amounts of moisture from the powder. After drying, the moisture content is ≤0.2wt%. After drying, it is sealed in packaging and stored in a dry and ventilated warehouse to avoid moisture absorption.

[0077] In this invention, the combustion products obtained by ammonia-assisted combustion are crushed and sieved to obtain powder with uniform particle size; magnetic separation secondary impurity removal can remove iron impurities that were not completely separated during calcination, further improving the purity of the powder; airflow classification purification can remove fine impurities and unqualified particles in the powder, ensuring that the powder particle size meets the requirements of high Al2O3 raw powder for refractory materials; finally, high-purity, uniformly sized high α-phase alumina raw powder is obtained.

[0078] This invention discloses a method for preparing high α-phase alumina powder using wet denitrification of aluminum ash and synergistic self-propagating process. The method uses industrial solid waste aluminum ash as raw material and follows a process route of raw material pretreatment – ​​pelletizing and granulation – wet denitrification (water-steam reaction) – self-propagating initiation high-temperature calcination – ammonia-assisted combustion – desalination and purification – crushing and screening. It utilizes the rapid reaction of AlN with water at 120-150℃ to produce aluminum hydroxide and ammonia, offering advantages such as fast reaction rate and high conversion rate. Furthermore, ammonia can be used as fuel for assisted combustion, achieving energy recovery. The method also allows for control of reaction temperature, water-steam injection rate, and... With sufficient contact time, the AlN conversion rate is ≥99%, and the AlN content after denitrification is ≤1%. Elemental Al in aluminum ash can be ignited by a self-propagating initiator at 450~550℃, releasing a large amount of heat and rapidly raising the kiln temperature without requiring additional energy consumption. The combustion of ammonia mixed with air can raise the kiln tail temperature to 1300~1500℃. At this temperature, the salt in the aluminum ash can be completely volatilized and separated. At the same time, Al2O3 and aluminum hydroxide can be directionally converted into α-alumina, with a salt removal rate ≥98% and salt residue ≤0.3%. This method achieves efficient removal of AlN from aluminum ash, salt volatilization and separation, and directional generation of α-alumina, ultimately preparing high α-phase alumina raw powder that meets the requirements of refractory materials. The prepared high α-phase alumina raw powder has an α-alumina content of ≥90% and an iron impurity content of ≤0.5%, meeting the requirements for raw materials of high-alumina refractory materials. It can be directly used to produce various refractory products, solving the technical pain point of poor refractory material performance caused by AlN and salt residues in aluminum ash. It achieves an organic combination of efficient utilization of aluminum ash resources and low-cost preparation of refractory materials. It has the advantages of simple process, low energy consumption, high product purity, environmental protection and energy saving. The technical principle is feasible and suitable for large-scale industrial application.

[0079] This invention removes impurities such as Fe2O3 and SiO2 through raw material pretreatment, which can prevent them from reacting with Al2O3 and generating useless impurity products; controlling the wet denitrification temperature and water vapor injection amount can prevent incomplete AlN reaction and reduce ammonia leakage; controlling the temperature of self-propagating combustion and ammonia-assisted combustion can prevent excessive growth of α-alumina grains, while ensuring complete salt volatilization, thereby improving reaction selectivity and product purity.

[0080] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments. The embodiments of this application are only examples, and all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0081] The basic parameters of the aluminum ash, self-propagating initiator, and other reagents used in the following examples and comparative examples are as follows: 1. Aluminum ash (produced from industrial electrolytic aluminum): AlN mass content 10%, elemental Al mass content 6%, Al2O3 mass content 60%, total mass content of sodium chloride and potassium chloride 5%, Fe2O3 mass content 2.0%, SiO2 mass content 2.5%, the remainder being inert impurities; 2. The self-propagating initiator is a mixture of potassium nitrate and nitrogen-rich aluminum ash, wherein the potassium nitrate has a purity of 98.5% (>98%), the nitrogen-rich aluminum ash contains 49% alumina, 15% elemental aluminum, 28% aluminum nitride, and a small amount of inert impurities, and the mixing mass ratio of potassium nitrate to nitrogen-rich aluminum ash is 4:1. 3. Other reagents: Deionized water (conductivity ≤10μS / cm), sodium carboxymethyl cellulose (binder, purity 99%); 4. Equipment parameters: pre-denitrification reactor speed 10 r / min, rotary kiln speed 8 r / min, 4 atomizing nozzles.

[0082] Example 1 S1. Select 100kg of aluminum ash and feed it into a jaw crusher to crush it to a particle size ≤10mm. After crushing, use a 10-mesh sieve to remove impurities. Then feed it into a planetary ball mill for grinding, with a ball-to-material ratio of 9:1, a rotation speed of 400r / min, and a grinding time of 2.5h, until the particle size is ≤75μm. Then feed it into a high-intensity magnetic separator for magnetic separation (temperature 25℃, intensity 0.35T, 2 times, 15min each time). After magnetic separation, the iron impurity content in the aluminum ash is 0.6wt%. The magnetically separated aluminum ash is then screened through a 130-mesh ultrasonic sieve (power 200W) to obtain 93kg of pretreated aluminum ash.

[0083] S2. The pretreated aluminum ash is fed into a pre-denitrification reactor (filling thickness is 12cm), heated to 120℃ at a rate of 5℃ / min, then heated to 135℃ at a rate of 2.5℃ / min, with a pressure of 0.08MPa, and held at the temperature for 2 hours. At the same time, atomized water vapor (atomized particle size 10-15μm, injection amount 9kg) is injected to obtain denitrified aluminum ash and ammonia gas. The ammonia gas is cooled, purified by dust removal, and collected for later use (purity 98.2%). The mass content of AlN in the denitrified aluminum ash particles is 0.8%. The ammonia gas is cooled to 90℃ and stored for later use.

[0084] S3. Denitrified aluminum ash and deionized water are mixed at a ratio of 100:10 (93 kg aluminum ash and 9.3 kg water), and 0.2 kg sodium carboxymethyl cellulose is added. The mixture is stirred at 15 r / min for 20 min. The mixed material is then placed in a drum granulator for granulation (ambient temperature 30℃, ambient humidity 50%, rotation speed 15 r / min, time 30 min) to obtain spherical particles with a particle size of 4-6 mm. The spherical particles are then dried with hot air at 85℃ for 0.8 h to obtain aluminum ash particles with a moisture content of 2.5 wt%.

[0085] S4. The cooled denitrified aluminum ash particles are mixed with a self-propagating initiator (potassium nitrate: nitrogen-rich aluminum ash = 4:1) at a ratio of 100:4 (88 kg aluminum ash and 3.52 kg initiator), and stirred for 18 min. The mixture is then fed into a rotary kiln and heated from 25 °C to 300 °C at a rate of 6 °C / min, then to 400 °C at a rate of 4 °C / min, and finally to 560 °C at a rate of 2.5 °C / min. The initiator ignites elemental Al, and the temperature in the middle of the kiln reaches 1200 °C, which is then held for 3 h. Ammonia gas is preheated to 250 °C and air is preheated to 350 °C, and then mixed at a volume ratio of 1:10. The mixture is then injected into the kiln tail for combustion, and the kiln tail temperature reaches 1450 °C, which is held for 1.5 h. After the salt volatilizes, it is condensed and recovered to obtain 4.8 kg of mixed salt. The calcined product is cooled to room temperature, and the salt content is 0.2%.

[0086] S5. The calcined product is fed into an impact crusher and crushed to a particle size ≤100μm; 190-mesh ultrasonic sieving (power 350W, frequency 30kHz) with a pass rate of 98.5%; secondary magnetic separation (strength 0.35T, 1 time, 10min) with an iron impurity content of 0.4%; air classification (speed 2500r / min, air velocity 20m / s) to obtain 58.2kg of high α-phase alumina raw powder for refractory materials.

[0087] Testing revealed that the high α-phase alumina raw powder contained 92.3% α-alumina, 0.7% AlN, 0.2% salt residue, and 0.4% iron impurities, with uniform particle size, meeting the standards for high Al2O3 raw powder for refractory materials. The AlN conversion rate was 92%, the salt removal rate was 96%, and the solid waste resource utilization rate was 98.5%.

[0088] Example 2 S1. Select 100kg of aluminum ash and feed it into a jaw crusher to crush it to a particle size ≤10mm. After crushing, use a 10-mesh sieve to remove impurities. Then feed it into a planetary ball mill for grinding at a ball-to-material ratio of 10:1, a rotation speed of 450r / min, and a time of 3h, until the particle size is ≤75μm. Then feed it into a high-intensity magnetic separator for magnetic separation (temperature 25℃, intensity 0.4T, 3 times, 12min each time). After magnetic separation, the iron impurity content in the aluminum ash is 0.5wt%. The magnetically separated aluminum ash is then screened through a 140-mesh ultrasonic sieve (power 200W) to obtain 91kg of pretreated aluminum ash.

[0089] S2. The pretreated aluminum ash is fed into a pre-denitrification reactor (filling thickness is 12cm), heated to 120℃ at a rate of 5℃ / min, then heated to 140℃ at a rate of 2.5℃ / min, with a pressure of 0.08MPa, and kept at a constant temperature for 2.5h. Atomized water vapor (atomized particle size 8-12μm, injection amount 10kg) is injected to obtain denitrified aluminum ash and ammonia gas. The ammonia gas is cooled, purified by dust removal, and collected for later use (purity 98.5%). The mass content of AlN in the denitrified aluminum ash is 0.6%. It is cooled to 85℃ and stored for later use.

[0090] S3. Mix denitrified aluminum ash and deionized water at a ratio of 100:12 (91 kg aluminum ash and 10.92 kg water), add 0.22 kg sodium carboxymethyl cellulose, and stir at 20 r / min for 22 min. Place the mixed material in a disc granulator for granulation (ambient temperature 32℃, ambient humidity 55%, rotation speed 20 r / min, time 25 min) to obtain spherical particles with a particle size of 5-7 mm. Dry the spherical particles with hot air at 90℃ for 0.6 h to obtain aluminum ash particles with a moisture content of 2.2 wt%.

[0091] S4. The cooled denitrified aluminum ash particles are mixed with a self-propagating initiator (potassium nitrate: nitrogen-rich aluminum ash = 5:1) at a ratio of 100:5 (86 kg aluminum ash and 4.3 kg initiator), and stirred for 16 min. The mixture is then fed into a rotary kiln and heated from 25 °C to 300 °C at a rate of 6 °C / min, then to 400 °C at a rate of 4 °C / min, and finally to 580 °C at a rate of 2.2 °C / min. The initiator ignites elemental Al, and the temperature in the middle of the kiln rises to 1250 °C, which is held for 2.5 h. Ammonia gas is preheated to 280 °C through a preheater, and air is preheated to 380 °C through a preheater. The mixture is then mixed at a volume ratio of 1:11 and injected into the kiln tail for combustion. The kiln tail temperature rises to 1480 °C and is held for 1.2 h. After the salts volatilize, they are condensed and recovered to obtain 4.7 kg of mixed salt. The calcined product is cooled to room temperature, and the salt content is 0.15%.

[0092] S5. The calcined product is fed into an airflow crusher to be crushed to a particle size ≤100μm; 200-mesh ultrasonic sieving (power 350W, frequency 30kHz) with a pass rate of 99%; secondary magnetic separation (intensity 0.38T, 1 time, 9min) with an iron impurity content of 0.35%; airflow classification (speed 2800r / min, airflow velocity 22m / s) to obtain 57.8kg of high α-phase alumina raw powder for refractory materials.

[0093] Testing revealed that the high α-phase alumina powder contained 93.1% α-alumina, 0.5% AlN, 0.15% salt residue, and 0.35% iron impurities; the AlN conversion rate was 94%, the salt removal rate was 97%, and the solid waste resource utilization rate was 98.8%; adjusting the initiator ratio improved both the reaction efficiency and the product purity.

[0094] Example 3 S1. Select 100kg of aluminum ash and feed it into a jaw crusher to crush it to a particle size ≤10mm. After crushing, use a 10-mesh sieve to remove impurities. Then feed it into a planetary ball mill for grinding at a ball-to-material ratio of 8:1, a rotation speed of 380r / min, and a time of 2.2h until the particle size ≤75μm. Then feed it into a high-intensity magnetic separator for magnetic separation (temperature 25℃, intensity 0.32T, 2 times, 16min each time). After magnetic separation, the iron impurity content in the aluminum ash is 0.7wt%. The magnetically separated aluminum ash is then screened through a 120-mesh ultrasonic sieve (power 200W) to obtain 92kg of pretreated aluminum ash.

[0095] S2. The pretreated aluminum ash is fed into a pre-denitrification reactor (filling thickness is 13cm), heated to 120℃ at a rate of 5℃ / min, then heated to 130℃ at a rate of 2.5℃ / min, with a pressure of 0.09MPa, and held at the same temperature for 1.8h. At the same time, atomized water vapor (atomized particle size 12-18μm, injection amount 8kg) is injected to obtain denitrified aluminum ash and ammonia gas. The ammonia gas is cooled, purified by dust removal, and collected for later use (purity 98.1%). The mass content of AlN in the denitrified aluminum ash is 0.9%, and it is cooled to 95℃ for later use.

[0096] S3. Pre-treated aluminum ash and deionized water are mixed at a ratio of 100:9 (92 kg aluminum ash and 8.28 kg water), without adding binder, and stirred at 15 r / min for 18 min. The mixed material is then placed in a drum granulator for granulation (ambient temperature 28℃, ambient humidity 45%, rotation speed 18 r / min, time 35 min) to obtain spherical particles with a particle size of 3-5 mm. The spherical particles are then dried with hot air at 82℃ for 0.9 h to obtain aluminum ash particles with a moisture content of 2.8 wt%.

[0097] S4. The cooled denitrified aluminum ash particles are mixed with a self-propagating initiator (potassium nitrate: nitrogen-rich aluminum ash = 3:1) at a ratio of 100:3 (87 kg aluminum ash and 2.61 kg initiator), and stirred for 19 min. The mixture is then fed into a roller kiln and heated from 25 °C to 300 °C at a rate of 6 °C / min, then to 400 °C at a rate of 4 °C / min, and finally to 580 °C at a rate of 2.5 °C / min. The initiator ignites elemental Al, and the temperature in the middle of the kiln reaches 1150 °C, which is then held for 3.5 h. Ammonia gas is preheated to 220 °C and air is preheated to 320 °C, and then mixed at a volume ratio of 1:9. The mixture is then injected into the kiln tail for combustion, and the kiln tail temperature reaches 1420 °C, which is held for 1.8 h. 4.6 kg of mixed salt is recovered, and the salt content of the calcined product is 0.25%.

[0098] S5. The calcined product was crushed to a particle size ≤100μm using an impact crusher; ultrasonic screening (power 350W, frequency 30kHz) with a pass rate of 98% was performed; secondary magnetic separation (intensity 0.32T, 2 times, 8min) was performed, with an iron impurity content of 0.45%; air classification (speed 2200r / min, air velocity 18m / s) was performed to obtain 56.9kg of high α-phase alumina raw powder for refractory materials.

[0099] Testing revealed that the high α-phase alumina powder contained 91.5% α-alumina, 0.8% AlN, 0.25% salt residue, and 0.45% iron impurities. The AlN conversion rate was 91%, the salt removal rate was 95%, and the solid waste resource utilization rate was 98.2%. In the absence of a binder, the particle formability decreased slightly, but this did not affect the overall process and product quality.

[0100] Example 4 S1. Select 100kg of aluminum ash and feed it into a jaw crusher to crush it to a particle size ≤10mm. After crushing, use a 10-mesh sieve to remove impurities. Then feed it into a planetary ball mill for grinding, with a ball-to-material ratio of 10:1, a rotation speed of 420r / min, and a grinding time of 2.8h, until the particle size is ≤75μm. Then feed it into a high-intensity magnetic separator for magnetic separation (temperature 25℃, intensity 0.38T, 2 times, 14min each time). After magnetic separation, the iron impurity content in the aluminum ash is 0.55wt%. The magnetically separated aluminum ash is then screened through a 135-mesh ultrasonic sieve (power 200W) to obtain 92.5kg of pretreated aluminum ash.

[0101] S2. The pretreated aluminum ash is fed into a pre-denitrification reactor (filling thickness of 12cm), heated to 120℃ at a rate of 5℃ / min, then heated to 138℃ at a rate of 2.5℃ / min, with a pressure of 0.1MPa, and held at the same temperature for 2.2h. Atomized water vapor (temperature 148℃, atomized particle size 9-14μm, injection amount 9.5kg) is injected to obtain denitrified aluminum ash and ammonia gas. The ammonia gas is cooled, purified by dust removal, and collected for later use (purity 98.3%). The mass content of AlN in the denitrified aluminum ash is 0.7%. It is cooled to 88℃ and stored for later use.

[0102] S3. Denitrified aluminum ash and deionized water are mixed at a ratio of 100:11 (92.5 kg aluminum ash and 10.175 kg water), and 0.21 kg sodium carboxymethyl cellulose is added. The mixture is stirred at 15 r / min for 21 min. The mixed material is then placed in a drum granulator for granulation (ambient temperature 31℃, ambient humidity 52%, rotation speed 15 r / min, time 28 min) to obtain spherical particles with a particle size of 4-7 mm. The spherical particles are then dried with hot air at 88℃ for 0.7 h to obtain aluminum ash particles with a moisture content of 2.4 wt%.

[0103] S4. The cooled denitrified aluminum ash particles are mixed with a self-propagating initiator (potassium nitrate: nitrogen-rich aluminum ash = 4.5:1) at a ratio of 100:5 (87.5 kg aluminum ash and 4.375 kg initiator), and stirred for 17 min. The mixture is then fed into a rotary kiln and heated from 25 °C to 300 °C at a rate of 6 °C / min, then to 400 °C at a rate of 4 °C / min, and finally to 590 °C at a rate of 2.5 °C / min. The initiator ignites elemental Al, and the temperature in the middle of the kiln reaches 1220 °C, which is then held for 2.8 h. Ammonia gas is preheated to 260 °C via a preheater, and air is preheated to 360 °C. The mixture is then mixed at a volume ratio of 1:10.5 and injected into the kiln tail for combustion. The kiln tail temperature reaches 1460 °C and is held for 1.4 h. After the salts volatilize, they are condensed and recovered to obtain 4.75 kg of mixed salt. The calcined product is cooled to room temperature, and the salt content is 0.18%.

[0104] S5. The calcined product is fed into an airflow crusher to be crushed to a particle size ≤100μm; ultrasonic screening (power 350W, frequency 30kHz) with a pass rate of 98.8% is performed; secondary magnetic separation (strength 0.36T, 1 time, 9.5min) is performed, with an iron impurity content of 0.38%; airflow classification (speed 2600r / min, airflow velocity 21m / s) is performed to obtain 57.6kg of high α-phase alumina raw powder for refractory materials.

[0105] Testing revealed that the high α-phase alumina powder contained 92.8% α-alumina, 0.6% AlN, 0.18% salt residue, and 0.38% iron impurities; the AlN conversion rate was 93%, the salt removal rate was 96.5%, and the solid waste resource utilization rate was 98.6%.

[0106] Comparative Example 1 The difference from Example 1 is that in S3, the pretreated aluminum ash is fed into the pre-denitrification reactor, heated to 135°C in stages, and kept at a constant temperature for 2 hours without spraying mist water vapor; the rest is the same as in Example 1.

[0107] Testing revealed that the AlN content in the wet denitrification product was only 8.2%, with an AlN conversion rate of only 18%. The ammonia production was only 17% of that in Example 1, and the kiln tail temperature during ammonia-assisted combustion only reached a maximum of 1150℃, which was insufficient to meet the requirements for salt volatilization and α-alumina formation. The final α-phase alumina raw powder for refractory materials contained 72.1% α-alumina, 7.8% AlN, 3.5% salt residue, and 0.8% iron impurities, which were far from meeting the standards for high Al2O3 raw powder for refractory materials. The solid waste resource utilization rate was only 75.3%, with a large amount of nitrogen remaining in the aluminum ash, which could easily lead to ammonia pollution during subsequent treatment.

[0108] It is evident that without the injection of mist-like water vapor, AlN cannot fully react with water, resulting in extremely low AlN conversion rate, insufficient ammonia production, failure to meet kiln tail temperature standards, ineffective salt removal, substandard product quality, and environmental hazards.

[0109] Comparative Example 2 The difference from Example 1 is that in S4, no self-propagating initiator is added, and the cooled denitrified aluminum ash particles are directly fed into the rotary kiln, heated in stages to 500°C, and kept at a constant temperature for 3 hours. Without an initiator, combustion occurs, and elemental aluminum cannot be ignited; the rest is the same as in Example 1.

[0110] Testing revealed that the highest temperature in the middle of the kiln only reached 680℃, which was insufficient to achieve spontaneous combustion of elemental aluminum, nor could it promote the decomposition of aluminum hydroxide and the crystallization of Al2O3. The final calcined product had a complex composition, containing α-alumina (35.2%), aluminum hydroxide (28.7%), aluminum nitride (7.5%), unreacted elemental aluminum (10.3%), and other impurities. No qualified high-Al2O3 raw material for refractory materials was produced. The salt content was 4.1%, and the iron impurity content was 0.9%, which completely failed to meet the process requirements.

[0111] It is evident that without the addition of a self-propagating initiator, the elemental aluminum in the aluminum ash cannot be spontaneously combusted. Insufficient kiln temperature prevents the various reactions from proceeding normally, resulting in a chaotic product composition and making it impossible to prepare high α-phase alumina raw powder for refractory materials.

[0112] Comparative Example 3 The difference from Example 1 is that in S5, the collected ammonia gas is not injected into the kiln tail for combustion, and the kiln temperature is maintained solely by the heat of spontaneous combustion of elemental aluminum. All other aspects are the same as in Example 1.

[0113] Testing revealed that the kiln tail temperature only reached a maximum of 1180℃, failing to meet the requirement of 1300-1500℃; the removal rate of chloride salts (sodium chloride, potassium chloride) in the aluminum ash was only 62%, with a salt residue of 1.9%; the final high α-phase alumina raw powder contained 78.5% α-alumina, 1.2% AlN, 1.8% salt residue, and 0.5% iron impurities, which did not meet the standard for high Al2O3 raw powder for refractory materials; the solid waste resource utilization rate was 82.7%, and the α-alumina content in the finished product was far lower than that in Example 1.

[0114] It is evident that without supplemental ammonia combustion, the kiln tail temperature cannot meet the requirements, the chloride removal rate is low, the salt residue is high, the α-alumina formation is insufficient, and the purity and performance of the product cannot meet the requirements for refractory material raw materials.

[0115] Comparative Example 4 The difference from Example 1 is that in S4, the purity of potassium nitrate in the self-propagating initiator is 97% (<98%), and the mixing mass ratio of potassium nitrate to nitrogen-rich aluminum ash is 2:1 (which does not meet the requirement of 3:1-5:1). All other aspects are the same as in Example 1.

[0116] Testing revealed that the initiator had low combustion efficiency, and the ignition time for elemental aluminum was extended by 45 minutes compared to Example 1. The highest temperature in the middle of the kiln only reached 1050℃. After 3 hours of constant-temperature calcination, the elemental aluminum content was still 1.8%, indicating incomplete combustion. The final high-α phase alumina powder contained 83.2% α-alumina, 1.5% AlN, 0.8% salt residue, and 0.6% iron impurities. The AlN conversion rate was 85%, the salt removal rate was 88%, and the solid waste resource utilization rate was 90.5%. However, the product quality did not meet the standards.

[0117] It is evident that insufficient purity or incorrect ratio of potassium nitrate in the initiator will reduce the initiation efficiency, leading to incomplete combustion of elemental aluminum, insufficient kiln temperature, and affecting the purity and performance of the product.

[0118] Comparative Example 5 The difference from Example 1 is that pelletizing is not performed; that is, the denitrified aluminum ash is directly fed into the kiln for self-propagation and ammonia-assisted combustion at high temperature. All other aspects are the same as in Example 1.

[0119] Testing revealed severe agglomeration of aluminum ash powder during high-temperature calcination. During self-propagating combustion, powder agglomeration led to localized excessively high and insufficient temperatures, resulting in uneven combustion of elemental aluminum. The final high-α phase alumina powder contained 85.7% α-alumina, 2.1% AlN, 0.7% salt residue, and 0.55% iron impurities, with uneven particle size and some particles agglomerated. The AlN conversion rate was 77%, the salt removal rate was 90%, and the solid waste resource utilization rate was 92.1%.

[0120] It is evident that without pelletizing, the aluminum ash agglomerates during the high-temperature treatment process, resulting in uneven reactions, incomplete combustion of elemental aluminum, and failure to meet the requirements for product purity and particle size.

[0121] Although preferred embodiments of the invention have been shown and described, it is conceivable that those skilled in the art can devise various modifications to the invention within the spirit and scope of the appended claims.

Claims

1. A method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash and synergistic self-propagation, characterized in that, Includes the following steps: S1. Pre-treat the aluminum ash to obtain pre-treated aluminum ash; S2. Spray water vapor into the pretreated aluminum ash to carry out a wet denitrification reaction and recover ammonia gas, and obtain denitrified aluminum ash. S3. Granulate and dry the denitrified aluminum ash to obtain denitrified aluminum ash particles; S4. Mix the denitrified aluminum ash particles with a self-propagating initiator, and perform self-propagating initiation and ammonia-assisted combustion high-temperature calcination to obtain high α-phase alumina particles. S5. The high α phase alumina particles are crushed and ground to obtain high α phase alumina raw powder.

2. The method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash and synergistic self-propagation according to claim 1, characterized in that, In S1, the pretreatment includes: crushing aluminum ash to a particle size ≤10mm, and then sequentially performing grinding, magnetic separation for impurity removal, sieving, and drying.

3. The method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash and synergistic self-propagation according to claim 2, characterized in that, The grinding method is ball milling, and the ball milling process includes: a ball-to-material ratio of 8:1 to 11:1, a grinding speed of 350 to 480 r / min, and a grinding time of 2 to 3.5 hours; The conditions for magnetic separation to remove impurities are as follows: magnetic separation intensity is 0.3~0.45T, magnetic separation temperature is 10~30℃, magnetic separation is performed 2~3 times, and the time for each magnetic separation is 10~18min. The sieve mesh size for sieving is 120-150 mesh.

4. The method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash and synergistic self-propagation according to claim 1, characterized in that, In S2, the amount of water vapor injected is 5% to 12% of the pretreated aluminum ash, the water vapor is saturated steam or superheated steam, the atomized particle size of the water vapor is 5 to 20 μm, and the conditions of the wet denitrification reaction are: temperature 120 to 150℃, time 1.5 to 3 h, and pressure 0.02 to 0.1 MPa.

5. The method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash and synergistic self-propagation according to claim 1, characterized in that, In S3, the amount of water added during granulation is 5-12% of the mass of the denitrified aluminum ash. The granulation process also includes the addition of a binder, which includes sodium carboxymethyl cellulose and / or starch. The granulation conditions are: ambient temperature of 25-35℃, ambient humidity of 40%-60%, rotation speed of 5-20 r / min, and time of 20-40 min.

6. The method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash and synergistic self-propagation according to claim 1, characterized in that, In S4, the mass ratio of the denitrified aluminum ash particles to the self-propagating initiator is 100:(2~6); the self-propagating initiator includes potassium nitrate and nitrogen-rich aluminum ash; in the nitrogen-rich aluminum ash, the mass content of elemental aluminum is 10%~20%, the mass content of aluminum nitride is 20%~35%, and the mass content of alumina is 40%~60%; the mass ratio of potassium nitrate to the nitrogen-rich aluminum ash is (3~5):1; the self-propagating initiation conditions are: heating from 10~30℃ to 300℃ at a heating rate of 5~8℃ / min, then heating to 400~450℃ at a heating rate of 3~5℃ / min, and then heating to 550~590℃ at a heating rate of 2~3℃ / min; the calcination conditions are: temperature of 1100~1300℃ and time of 2~4h.

7. The method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash and synergistic self-propagation according to claim 1, characterized in that, In S4, the ammonia-assisted combustion process includes: Preheated ammonia and preheated air are mixed and then introduced into a high-temperature calcining furnace for ammonia-assisted combustion.

8. The method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash and synergistic self-propagation according to claim 7, characterized in that, The temperature of the preheated ammonia is 200~300℃; the temperature of the preheated air is 300~400℃; the volume ratio of the preheated ammonia to the preheated air is 1:(8~12); the conditions for ammonia-assisted combustion are: temperature 1300~1500℃, time 1~2h.

9. The method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash and synergistic self-propagation according to claim 1, characterized in that, In step S5, after the ammonia-assisted combustion is completed, the process further includes: crushing the product obtained from the ammonia-assisted combustion to a particle size ≤100μm, and then sequentially screening, purifying, removing impurities and unqualified particles.

10. The method for preparing high α-phase alumina raw powder by wet denitrification of aluminum ash and synergistic self-propagation according to claim 9, characterized in that, The sieve mesh size for the screening is 180~200 mesh; The purification method is two-stage magnetic separation for impurity removal. The conditions for the two-stage magnetic separation are: magnetic separation intensity of 0.3~0.4T, magnetic separation number of times of 1~2 times, and magnetic separation time of 8~12min for each time. The method for removing impurities and unqualified particles is to feed the magnetically separated powder into an air classifier, with a classification speed of 2000-3000 r / min and a classification airflow velocity of 15-25 m / s.